2018
DOI: 10.1111/bcp.13586
|View full text |Cite
|
Sign up to set email alerts
|

An update on the clinical evidence that supports biosimilar approvals in Europe

Abstract: AimSponsors and regulators have more than 10 years of experience with the development of biosimilars in Europe. However, the regulatory pathway is still evolving. The present article provides an update on biosimilar development in practice by reviewing the clinical development programmes of recently approved biosimilars in Europe.MethodsWe used the European public assessment reports (EPARs) which are published by the European Medicines Agency (EMA) for a comparison of the clinical development programmes of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…Despite this variability in QA reporting, pCQAs were most frequently and consistently reported by EU regulators in EPARs. The variation in QA report-ing between EPARs is consistent with the variability in reporting clinical data, which was explained by the flexibility in regulatory requirements (i.e., a case-by-case basis) [43,44]. However, such flexibility cannot explain the variability in reporting of QAs and pCQAs for biosimilars, particularly those containing the same active substance and compared to the same reference biological (e.g., Humira ® in the case of adalimumab), that were assessed based on the same regulatory standards for establishing biosimilarity.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Despite this variability in QA reporting, pCQAs were most frequently and consistently reported by EU regulators in EPARs. The variation in QA report-ing between EPARs is consistent with the variability in reporting clinical data, which was explained by the flexibility in regulatory requirements (i.e., a case-by-case basis) [43,44]. However, such flexibility cannot explain the variability in reporting of QAs and pCQAs for biosimilars, particularly those containing the same active substance and compared to the same reference biological (e.g., Humira ® in the case of adalimumab), that were assessed based on the same regulatory standards for establishing biosimilarity.…”
Section: Discussionsupporting
confidence: 62%
“…The European public assessment report (EPAR) is an unbiased source through which the EMA publishes and broadcasts information to stakeholders about regulatory assessments for all medicinal products approved by the European Commission (EC) [37]. Previous studies have provided an in-depth overview of the clinical evidence reported in EPARs that supports approval of biosimilars in general [43,44] and approval of adalimumab biosimilars in particular [45]. These studies have shown that variations exist in reporting clinical data that confirm the biosimilarity of biosimilars to a reference biological, but they have not explored the reporting of the QAs that are the basis of biosimilar approval.…”
Section: Introductionmentioning
confidence: 99%
“…15 It has also been documented that both the FDA and the EMA have approved less complex therapeutic proteins via abbreviated pathways. 3,16 The adoption of this simplified and pro-competitive approach in the global south would be facilitated if WHO amended its guidelines, instead of brand names reduces information asymmetry. 17 The use of INN on prescription, dispensation, labels, and pharmaceutical advertising is part of WHO's ethical criteria for medicinal drug promotion.…”
Section: Key Pointsmentioning
confidence: 99%
“…The EMA is moving slowly to revise the comparability paradigm, as commented before, 7 and some middle‐income countries, like Colombia and Brazil, have allowed simplification or even waivers of confirmatory trials in specific circumstances, too 15 . It has also been documented that both the FDA and the EMA have approved less complex therapeutic proteins via abbreviated pathways 3,16 …”
Section: The Triangle Of Technical Barriers Explainedmentioning
confidence: 99%
“…Recently, biological products have been used in therapies for certain cancers and rare diseases 1 . Due to complications in the development of these macromolecular medicines, the prices of innovative biological products are always high.…”
Section: Introductionmentioning
confidence: 99%